A frameshift mutation of TMPRSS3 in a Chinese family with non-syndromic hearing loss - Liang, Jingwen; Yu, Zhuoheng; Wang, Zhangxing; Chen, Jianxia; Liu, Yihuan; Yin, Zhaoqing; Xu, Ruihuan (Frontiers in Pediatrics, 2022)
Abstract Background: Deafness is the most common sensory defect in humans worldwide. Approximately 50% of cases are attributed to genetic factors, and about 70% are non-syndromic hearing loss (NSHL). Objectives: To identify clinically relevant gene variants associated with NSHL in a Chinese family using trio-based whole-exome sequencing (WES). Materials and Methods: WES was performed on the 18-month-old female proband, her parents, and 1010 healthy subjects. Gene variants specific to the family were identified by bioinformatics analysis and evaluated for their relevance to NSHL. Results: We identified a novel homozygous deletion (c.51delA) in exon 2 of the type II transmembrane serine protease 3 gene TMPRSS3, which resulted in a frameshift mutation just before the protein transmembrane domain (p.Q17fs). The deletion was present in the proband and her parents but not in the healthy controls. We also identified mutations with potential relevance to hearing loss in DCAF17, which encodes a protein of unknown function (c. T555A: p.H185Q), and ZNF276, which encodes zinc finger protein 276 (c.1350-2A>G).